Analytical prediction of initiation of ferroresonance modes. (April 2020) - Sa'ad Haji Bini, M; Ang, S P; Yeo, K S K; Khalil, A; Jaafar, S
Abstract: This research focuses on the impact of basic circuit parameters to the initiation of characteristic ferroresonance modes, which is a non-linear phenomenon, in single-phase power transformers. This non-linear phenomenon is investigated using an equivalent circuit of the transformer together with a circuit simulation. The basic circuit parameters investigated were iron core loss, circuit capacitance, and the source voltage. A mathematical method is used to calculate the critical boundary values of each parameter to avoid the occurrence of ferroresonance in the system. In this paper, an analytical method was used to predict the occurrence of ferroresonance while Matlab/Simulink simulation was used to determine the different ferroresonance modes in the power transformers. By varying the circuit parameters, different ferroresonance modes are observed and discussed.